2022
DOI: 10.17305/bjbms.2022.7677
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy attenuates osteoarthritis in mice by inhibiting chondrocyte pyroptosis and improving subchondral bone remodeling

Abstract: Osteoarthritis (OA) is an age-related degenerative disease characterized by cartilage degeneration and abnormal bone remodeling in the subchondral bone. Autophagy maintains cellular homeostasis by self-phagocytosis. However, the underlying mechanisms of autophagy on the pathological progression of OA are still unknown. This study assessed the effects of autophagy on cartilage and subchondral bone in a mouse OA model. A mouse OA model was induced using destabilization of the medial meniscus (DMM) surgery. Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Numerous pieces of evidence indicate that a crucial role is played by autophagy in the progression of OA ( Musumeci et al, 2015 ; Liu et al, 2021 ; Yan et al, 2022 ). Therefore, we analyzed the impacts of FKA on autophagy in IL-1β-treated mouse chondrocyte cells.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous pieces of evidence indicate that a crucial role is played by autophagy in the progression of OA ( Musumeci et al, 2015 ; Liu et al, 2021 ; Yan et al, 2022 ). Therefore, we analyzed the impacts of FKA on autophagy in IL-1β-treated mouse chondrocyte cells.…”
Section: Resultsmentioning
confidence: 99%
“…25 Autophagy, a protective mechanism of cells, is reported to participate in a variety of biological functions such as cell differentiation, cell proliferation, and apoptosis. 26,27 Yan et al 28 have proved that autophagy can attenuate OA in mice by suppressing chondrocyte pyroptosis and improving subchondral bone remodeling. Moreover, a study by Bay-Jensen et al 29 has confirmed that maintaining autophagy level in chondrocytes In recent years, increasing researchers have focused on the vital functions of NLRP3 inflammasome in immune-associated diseases, including OA.…”
Section: Discussionmentioning
confidence: 99%
“…At the level of gene expression, miR-107 [ 125 ], miR-140-5p, miR-155, miR-219a-5p [ 126 ], and miR-326 [ 127 ] can inhibit chondrocyte pyroptosis, potentially providing a new therapeutic modality. Preclinical studies have demonstrated that icariin [ 128 ], loganin [ 129 ], licochalcone Am [ 130 ], irisin [ 131 ], quercetin [ 126 ], morroniside [ 132 ], and rapamycin [ 133 ] inhibit the classical pyroptotic pathway and reduce chondrocyte death, suggesting future roles in the treatment of OA. In addition, combined treatment with antagonists of GSDMD (disulfiram) and HMGB1 (glycyrrhizic acid) can attenuate chondrocyte pyroptosis, inhibit inflammation, and promote chondrocyte proliferation in vitro, thereby suggesting a therapeutic approach for OA [ 134 ].…”
Section: Pyroptosis and Degenerative Diseases Of The Elderlymentioning
confidence: 99%